Effect of Organic Mulch on Pest, Disease and Productivity of Cayenne Pepper (Capsicum Frutescens L.) - Wildan Muhlison; Irwanto Sucipto; Hari Purnomo; I Nyoman Wijaya Paramudita; Nabilah Aulia Rohmah; Tri Wahyu Saputra; Syafina Pusparani (Postgraduate, University of Mataram, 2025)
Cayenne pepper (Capsicum frutescens L.) productivity is frequently limited by pest and disease pressure linked to reduced plant resistance from poor soil conditions and micronutrient deficiencies. This study evaluated whether different mulches mitigate disease incidence and improve growth and yield. Objectives were to quantify mulch effects on disease intensity, soil properties, vegetative growth, and fruit yield. A field experiment used a randomized block design with five treatments (P0 = no mulch; P1 = plastic; P2 = baglog; P3 = leaf litter; P4 = rice straw) and five replications. Measured variables included soil pH and moisture, pest population, pest attack intensity (%), disease attack intensity (%), and plant growth and productivity. Data were analyzed by ANOVA followed by Duncen further test (α = 0.05). Results showed that organic mulches reduced disease incidence to 17.2–19.2% versus 28.6% in the no-mulch control. Rice straw and leaf litter significantly improved soil pH and moisture retention; baglog and straw mulches increased branch number and further lowered disease incidence; plastic mulch produced the highest fruit weight per plant. In conclusion, organic mulches particularly rice straw and leaf litter enhance soil conditions and plant resilience, reducing disease and supporting productivity, while plastic mulch maximizes individual-plant yield.